On the computational security of randomized stream ciphers proposed by Mihaljević and Imai - Олексійчук, Антон Миколайович; Гришаков, Сергій Володимирович (Ukrainian Information Security Research Journal, 2015)
This paper yields a (computational) security analysis for a generic class of randomized stream ciphers based on joint employmentof encryption, error-correction coding, and dedicated random coding. We show that the security of these ciphers can be considerablyless than their designers claim. In contrast to the approach for security evaluation used before, our technique is significantly simplerand allows us to find out the code-theoretic sense of parameters that determine the security of these ciphers. We also proposeanother possible solution (based on nonlinear random coding) for design of randomized stream ciphers with enhanced security.